ECOLOGICAL CULTURE AS A COMPONENT OF MODERN MAN’S SPIRITUALITY - Skyba, Oksana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. The article is devoted to the study of the peculiarities of the formation of ecological culture of modern man. The chosen problem is actual in a crisis current ecological situation. The aim and tasks. This study is intended to trace the stages of the emergence of environmental ethics as a science, analyze the features of development and formation of modern ecological culture of the mankind. Research methods are general and special methods and approaches that enable to trace and take into account important aspects of the development and formation of the ecological culture of mankind. Research results. The global environmental problem of mankind has been in the spotlight of scientists in the late XX and early XXI century. Scientists have tried to rethink man's attitude to nature in terms of universal values. The formation of a certain attitude to nature is possible if man takes nature as a "world", a habitat determined by the level of development of the cultural-historical epoch and a certain type of practical activity. But nature for man is not only a habitat. It is home, a cathedral, which must be taken care of. Therefore, the focus on the idea of a holistic inalienable harmonious existence of man and nature, the extension of moral principles to nature is evident. Discussion. Nowadays, some scientists are on guard against scientific and technological progress overshadowing humanity's mind not so much to create new values but to deny the cultural heritage of the past. The point is that the fruits of the progress are not always good for humanity, being the initial cause of the most global problems. Conclusion. In modern society, it is necessary since childhood to cultivate a caring attitude to nature, to form the ecological culture to avoid the destructive consequences of man’s activity in relation to nature.